2018
DOI: 10.1016/j.jpainsymman.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Drugs Used for Euthanasia: A Repeated Population-Based Mortality Follow-Back Study in Flanders, Belgium, 1998–2013

Abstract: Physicians in Flanders are increasingly using the recommended drugs for euthanasia. This suggests that guidelines and training regarding the conduct and pharmacological aspects of euthanasia may have had important effects on the practice of euthanasia. However, the declining but persisting use of nonrecommended drugs requires further attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…It is important to note that research in Belgium and the Netherlands has shown that not all cases of euthanasia and assisted death are reported so these figures are likely underestimations of the actual extent of the practices (7). Some physicians who administer opiates with the intention of ending a person's life at their request do not recognize their actions as euthanasia, and in other cases physicians do not want to follow the prescribed procedures using recommended medication because their patient does not satisfy all the required conditions or because they find the procedure overly cumbersome (29).…”
Section: Mortality Follow-back Studies Among Attending Physiciansmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that research in Belgium and the Netherlands has shown that not all cases of euthanasia and assisted death are reported so these figures are likely underestimations of the actual extent of the practices (7). Some physicians who administer opiates with the intention of ending a person's life at their request do not recognize their actions as euthanasia, and in other cases physicians do not want to follow the prescribed procedures using recommended medication because their patient does not satisfy all the required conditions or because they find the procedure overly cumbersome (29).…”
Section: Mortality Follow-back Studies Among Attending Physiciansmentioning
confidence: 99%
“…The clinician is often not present when the patient administers the life-ending drugs in the US, usually by swallowing a lethal cocktail, however, in Belgium, the Netherlands and Luxembourg, physician presence is mandatory (5). The Dutch Medical Association has published guidelines on recommended and non-recommended drugs making it part of the professional conduct rules (29). In Belgium, pharmacists have published guidance on specific products and dosages and best practice information has been disseminated by the Life End Information Forum (LEIF) in Flanders, the Dutch-speaking part of Belgium (29).…”
Section: Drugs Used For Euthanasia and Assisted Suicidementioning
confidence: 99%
See 1 more Smart Citation
“…Relevantly, research from Belgium found that despite AD being legal, some doctors who report that their primary intention is to hasten death still use medications associated with palliative sedation (morphine or other opioids and/or benzodiazepine) rather than recommended medications to hasten death, and that use of these medications is often termed by doctors there as 'palliative sedation' or 'alleviation of pain and symptoms'. 28…”
Section: Discussionmentioning
confidence: 99%
“…One major caveat of studying MAiD practice through the reported cases is that it suffers from an under-reporting bias. Studies have estimated that, even several years after legalisation, from 1/5 (the Netherlands)4 to 1/3 (Belgium)5 cases is not reported. Hence, the advice is that this type of research should be combined with other forms of research indicated under the other recommendations.…”
Section: Study the Reported Cases In All Jurisdictions Where Maid mentioning
confidence: 99%